Copper(ii) carboxylate-cyclam complexes as thermally stable magnetic materials / Nur Syamimi Ahmad Tajidi - Nur Syamimi , Ahmad Tajidi (2014)

(untitled)
The objective of this research was to study the correlation between structure and physical properties of copper(II)-cyclam-alkylcarboxylate complexes, and the electronic effect of a substituent on the aromatic ring of copper(II)-cyclam-arylcarboxylate complexes. The alkylcarboxylate ligands were CnH2n+1COO (n = 6, 7, 9, 11, 13, 15) and CH3(CH2)7CH((CH2)5CH3), while the arylcarboxylate ligands were p-XC6H4COO (X = NH2, OH, OCH3, CH3, C≡N, H) and C6F5COO.